The persistence of current account balances and its determinants: The implications for global rebalancing - Erica Clower; Hiro Ito (Asian Development Bank Institute (ADBI), 2012)
This paper examines the statistical nature of the persistency of current account balances and its determinants. With the assumption that stationary current account series ensures the long-run budget constraint while countries may experience "local non-stationarity" in current account balances, we examine the dynamics of current account balances across a panel of 70 countries. We find that once we allow current account series to take regime shifts by applying a Markovswitching (MS) process, we are able not only to reject the unit root null hypothesis for a much increased number of countries than with standard linear unit root tests, but also to identify notable cross-country differences in the timing and duration of stationary and locally nonstationary regimes. Armed with the structural break dates the MS-ADF testing provides, we investigate the determinants of the different degrees of current account persistence. We find that emerging market countries with fixed exchange rate regime or countries with greater financial openness are more likely to enter a random walk regime, which is more evident among countries with current account deficits. For countries with all levels of income, trade openness decreases the likelihood of entering the random walk regime, presumably reducing the cost of current account adjustments. Also, countries with budget deficits tend to stay in stationary regimes, so do those with current account deficits, implying that markets force these countries to rebalance their current account imbalances. When we examine the determinants of various degrees of current account persistence, the type of exchange rate regimes no longer affects the extent of current account persistence. However, countries with greater trade or financial openness, or those with mounting pressure from real exchange rate misalignment tend to have a smaller degree of current account persistence while international reserves holding seems to contribute to a larger degree of persistence.
Keywords: F32; F41; 330; current account; financial liberalization; global imbalances; capital controls; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Stochastischer Prozess; Zeitreihenanalyse; Welt